Rosemary & Thyme. Series two [videorecording (DVD)] - Farnham, Brian; Sage, Gwennan; Langton, Simon; Kendal, Felicity; Ferris, Pam; Gunning, Chris (Acorn Media, 2005)
Rosemary Boxer and Laura Thyme, two middle-aged women, make a fresh start by opening a gardening business. Mysteries grow around these two gardening sleuths as they dig up trouble on the job and use investigative skills to get to the bottom of things. Series two includes episodes set in gardens on the French Riviera and Italy's Lugurian coast in addition to several fabulous gardens in England.